2012
DOI: 10.1071/rdv24n1ab38
|View full text |Cite
|
Sign up to set email alerts
|

38 Vitrification of Bos Taurus Indicus and Bos Taurus Indicus×bos Taurus Taurus Embryos Produced in the Presence or Absence of Fetal Calf Serum

Abstract: In vitro-produced Bos taurus indicus (zebu) and Bos taurus indicus × Bos taurus taurus (cross-bred) embryos behave differently when vitrified. The present experiment aimed to examine the effect of vitrification on embryos produced in the presence or absence of FCS. Cumulus-oocyte complexes (COC) were matured in TCM-199 and fertilized in human tubal fluid medium with frozen Nelore bull semen. On Day 1 (Day 0 = IVF), presumptive zygotes were cultured with SOFaa + BSA in the presence of FCS (Group 2.5%) or in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This factor is one of the reasons that led to our experiment to highlight the cleavage and blastocyst rates compared with the results in the literature. In addition, these results reinforce the differences in breeds observed between zebu and crossbreed, as they behaved differently in relation to the addition of FCS to the culture medium (Paschoal et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This factor is one of the reasons that led to our experiment to highlight the cleavage and blastocyst rates compared with the results in the literature. In addition, these results reinforce the differences in breeds observed between zebu and crossbreed, as they behaved differently in relation to the addition of FCS to the culture medium (Paschoal et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These adverse factors negatively impact ER functions and protein synthesis and folding, resulting in the activation of ER stress and the UPR signaling pathways in in vitro-produced embryos [ 14 , 15 , 16 , 17 ]. Furthermore, there is evidence that IVPEs are more sensitive to cryopreservation than in vivo derived from embryos [ 34 , 35 ] and that this reduced cryotolerance may be associated with the high lipid content present in the cytoplasm as well as the lipid profile of the cell membrane of these embryos [ 28 , 29 , 34 ]. Although TUDCA has been demonstrated to exert efficient cytoprotective activity in relieving ER stress [ 17 , 18 , 20 , 26 ], recent studies reported on its new potential and molecular modes of action as a weight-reducing agent, modulating lipid metabolism through or independently of ER modulation [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced post-warming cell viability is also associated with the abnormal amount and/or the type of lipids in the blastomeres that contributes to the occurrence of cryogenic fractures during the freezing process [ 28 , 34 ]. The cell membrane fluidity is related to the lipid profile and the capacity to support cryo-injuries during the cryopreservation process [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations